Tuning the In Vivo Transport of Anticancer Drugs Using Renal‐Clearable Gold Nanoparticles. (14th May 2019) - Peng, Chuanqi; Xu, Jing; Yu, Mengxiao; Ning, Xuhui; Huang, Yingyu; Du, Bujie; Hernandez, Elizabeth; Kapur, Payal; Hsieh, Jer‐Tsong; Zheng, Jie
Abstract: Precise control of in vivo transport of anticancer drugs in normal and cancerous tissues with engineered nanoparticles is key to the future success of cancer nanomedicines in clinics. This requires a fundamental understanding of how engineered nanoparticles impact the targeting‐clearance and permeation‐retention paradoxes in the anticancer‐drug delivery. Herein, we systematically investigated how renal‐clearable gold nanoparticles (AuNPs) affect the permeation, distribution, and retention of the anticancer drug doxorubicin in both cancerous and normal tissues. Renal‐clearable AuNPs retain the advantages of the free drug, including rapid tumor targeting and high tumor vascular permeability. The renal‐clearable AuNPs also accelerated body clearance of off‐target drug via renal elimination. These results clearly indicate that diverse in vivo transport behaviors of engineered nanoparticles can be used to reconcile long‐standing paradoxes in the anticancer drug delivery. Abstract : Lange bestehende Paradoxa beim Transport von Tumortherapeutika – z. B. effiziente Tumoradressierung vs. rasche Ausscheidung oder hohe Permeabilität vs. niedrige systemische Toxizität – können mit über die Niere ausscheidbaren Goldnanopartikeln (AuNPs) gelöst werden. Doxorubicin‐beschichtete AuNPs (DOX@AuNPs) behalten die rasche Tumoradressierung und hohe Tumorpermeabilität des freien Wirkstoffs bei, und Off‐Target‐DOX@AuNPs werden schneller vom Körper ausgeschieden als der freie Wirkstoff.